Tumor Spread Through Air Spaces Is an Independent Predictor of Recurrence-free Survival in Patients With Resected Lung Squamous Cell Carcinoma. (August 2017) - Kadota, Kyuichi; Kushida, Yoshio; Katsuki, Naomi; Ishikawa, Ryou; Ibuki, Emi; Motoyama, Mutsumi; Nii, Kazuhito; Yokomise, Hiroyasu; Bandoh, Shuji; Haba, Reiji
Abstract : Tumor spread through air spaces (STAS) is a newly recognized pattern of invasion in lung adenocarcinoma. However, clinical significance of STAS has not yet been characterized in lung squamous cell carcinoma. In this study, we investigated whether STAS could determine clinical outcome in Japanese patients with lung squamous cell carcinoma. We reviewed tumor slides from surgically resected lung squamous cell carcinomas (n=216). STAS was defined as tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. Tumors were evaluated for histologic subtypes, tumor budding, and nuclear diameter. Recurrence-free survival (RFS) was analyzed using the log-rank test and the Cox proportional hazards model. Tumor STAS was observed in 87 patients (40%), increasing incidence with lymph node metastasis ( P =0.037), higher pathologic stage ( P =0.026), and lymphatic invasion ( P =0.033). All cases with STAS showed a solid nest pattern. The 5-year RFS for patients with STAS was significantly lower than it was for patients without STAS in all patients ( P =0.001) and in stage I patients (n=134; P =0.041). On multivariate analysis, STAS was an independent prognostic factor of a worse RFS (hazard ratio=1.61; P =0.023). Patients with STAS had a significantly increased risk of developing locoregional and distant recurrences ( P =0.012 and 0.001, respectively). We found that tumor STAS was an independent predictor of RFS in patients with resected lung squamous cell carcinoma, and it was associated with aggressive tumor behavior.